(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
The age of change is often a rich fertile ground for ideas. Both Confucius and Socrates lived in times of great change. Their thoughts are the product of the turbulent times, the response to the changing society, and the embodiment of the spirit of the times. Both Confucius and Socrates, as masters of Eastern and Western civilizations, have left behind valuable intellectual resources for posterity.